Assessment of patient satisfaction and adherence to treatment with IOP-lowering medication in an innovative OSD bottle - D.P. Novikov; E.S. Kuznetsova (РМЖ "Клиническая офтальмология")
D.P. Novikov, E.S. Kuznetsova Diagnostic Center No. 7 (Ocular), St. Petersburg, Russian Federation Background: a significant proportion of patients with glaucoma require two or three IOP-lowering medications to achieve the target IOP. Factors that improve adherence to treatment include fixed-dose combinations (FDC) and preservative-free formulations. Good tolerability of long-term treatment and precise dosing are important prerequisites for the efficacy of glaucoma treatment. Recently, the ophthalmological armamentarium was replenished with preservative-free dorzolamide/timolol FDC containing sodium hyaluronate (Dorzial plus), thereby increasing adherence to prescribed therapy. Aim: to assess subjective difficulties in using the drug in an OSD bottle and to identify the most significant factors affecting treatment comfort and adherence to treatment. Patients and Methods: a questionnaire consisting of 9 questions was developed. Patients were surveyed in the outpatient setting. The survey involved 43 patients (32 women and 11 men). Questionnaires were completed anonymously without specifying personal data after 1 month of using the study drug. Results and Discussion: treatment comfort was rated "satisfied” and “very satisfied" by more than 90% of the respondents. In addition, more than 90% successfully dealt with drug dosing (1 drop from the OSD bottle). Difficulties in applying force when pressing the OSD bottle were rare, although a positive assessment of drug characteristics prevailed. When asked about continuing therapy, most respondents answered that they wanted to continue treatment with the prescribed drug. Conclusion: the survey demonstrated that Dorzial Plus has the necessary range of characteristics to ensure a high level of patient satisfaction and adherence to treatment. Keywords: adherence to treatment, primary open-angle glaucoma, OSD bottle, dorzolamide/timolol fixed-dose combination, preservative-free therapy, treatment comfort. For citation: Novikov D.P., Kuznetsova E.S. Assessment of patient satisfaction and adherence to treatment with IOP-lowering medication in an innovative OSD bottle. Russian Journal of Clinical Ophthalmology. 2023;23(4):192–196 (in Russ.). DOI: 10.32364/2311-7729-2023-23-4-3.